CLASSIFICATION OF AQAD IN SHARIA ECONOMIC LAW - Witro, Doli; Nuraeni, Neni; Januri, Muhammad Fauzan (Nurani, 2021)
As social beings, humans cannot be separated from each other to fulfill their daily needs. One of the relationships between one human being and another is manifested by an agreement. The agreement process is generally referred to as aqad or contract. Many parties who enter into contracts do not understand the rights and obligations they must fulfill, so even though they use the Islamic legal agreement system, the values ​​in this concept have not been fully implemented. This paper discusses the classification of aqad in sharia economic transactions, which is analyzed using the opinions of the mazhab scholars. This paper aims to explain the classification of aqad in sharia economic law. The research method used in this research is library research. In this case, the writer obtains literary sources through literature such as books, journals, and encyclopedias related to the theme being studied. This research is oriented towards discussing the urgency or importance of aqad in Islamic economic law. The data in the research are presented in a descriptive narrative way. The analysis technique used is the data analysis technique introduced by Miles and Huberman, namely data reduction, data presentation, and concluding. The results showed that aqad is an agreement in an agreement between two parties. In general, the classification is divided into two aqad/agreements, namely aqad tabarru’ and aqad tijarah.